Photosynthetic response to different light intensities and water status of two main Nothofagus species of southern Patagonian forest, Argentina - Peri, Pablo Luis; Martínez Pastur, Guillermo José; Lencinas, María Vanessa (Journal of Forest Science)
Net photosynthetic rate (A) and stomatal conductance (gs) of seedlings of Nothofagus. pumilio and N. antarctica leaves were measured at different light intensity (20, 150, 250, 500, 750, 1000, 1500 and 2200 µmol m-2 s-1 photosynthetic photon flux density, PPFD) and after 60 minutes of severe shade to determine the lag in the rise of photosynthesis rate from low to high irradiance levels (induction state). Also, A and gs were measured to evaluate the responses to water stress and the tolerance to waterlogging in the two species. N. pumilio had higher A values than N. antarctica for all light intensities measured with a maximum value of 16.8 µmol CO2 m-2 s-1 saturated at 1000 µmol m-2 s-1 PPFD. Values of gs for both Nothofagus species also declined as light intensity decreased at a rate of 0.0002 mol H2O m-2 s-1/µmol m-2 s-1 PPFD. The times required for full induction of A were 18 and 27 minutes after the increase of PPFD (full sun) for N. pumilio and N. antarctica, respectively. There was a negative relationship between A and water stress expressed as pre-dawn leaf water potential (ψlp) where the reduction in gs was the main factor that reduced A in both species. A reached a negative value from -17.0 bar for N. pumilio and from -27.0 bar for N. antarctica. Tolerance to waterlogging was related with changes in A and gs being N. antarctica was more tolerant. After 10 days of waterlogging the average decrease in A was 83% for N. pumilio and 65% for N. antarctica. These defined photosynthetic results of Nothofagus leaves to fluctuating light regimes, water stress and waterlogging could be used to estimate the responses of regeneration to environmental conditions under the dynamic of natural stands, after silviculture practices, and degraded sites for restoration plans. Fil: Peri, Pablo Luis. Universidad Nacional de la Patagonia Austral; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Martínez Pastur, Guillermo José. Consejo Nacional de Investigaciones Científicas y Técnicas. ...